n = 1 ∏ 2 0 1 6 sec ( 2 0 1 7 n π )
Evaluate the product above.
Given that the above is equal to a b where a is a prime number, find a + b .
Inspired by this problem when I solved it in 3 steps... All of which were wrong, but somehow I got the right answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
WolframAlpha
solve {product(sec(n pi/2017)), n=1 to 2016}=2^b
as a is prime use the first prime >1
b=2016 a+b=2018
Let T n be the nth Chebyshev Polynomial where T n ( cos ( x ) ) = cos ( n x )
We are looking at a product of 2017 terms from
n = 0 ∏ 2 0 1 6 sec ( 2 0 1 7 n π )
We can make each term a root of the polynomial T 2 0 1 7 ( n ) = 1
Now, the trick here is to realize that not every term of c o s ( n π ) is equal to 1. 1008 are odd n and are equal to -1. To accommodate this, we shift every odd term π to the right (we add \pi). This won't change the value of the equation so it won't change the polynomial value either.
Now, for the product of the roots, we need the constant term divided by the lead coefficient. The constant term will be -1 of course and the lead coefficient 2 n − 1 = 2 2 0 1 6
T 2 0 1 7 ( x ) − 1 = 2 2 0 1 6 x 2 0 1 7 + stuff − 1
Product of roots
2 2 0 1 6 1
So sec ( x ) is
2 2 0 1 6
n = 1 ∏ 2 0 1 6 sec ( 2 0 1 7 n π ) = n = 1 ∏ 2 0 1 6 cos ( 2 0 1 7 n π ) 1 x = n = 1 ∏ 2 0 1 6 cos ( 2 0 1 7 n π ) y = n = 1 ∏ 2 0 1 6 sin ( 2 0 1 7 n π ) x . y = n = 1 ∏ 2 0 1 6 sin ( 2 0 1 7 n π ) cos ( 2 0 1 7 n π ) x . y = 2 1 n = 1 ∏ 2 0 1 6 sin ( 2 0 1 7 2 n π ) = ( 2 1 ) 2 0 1 6 [ sin ( 2 0 1 7 2 π ) sin ( 2 0 1 7 4 π ) ⋯ sin ( 2 0 1 7 1 4 π ) sin ( 2 0 1 7 1 6 π ) sin ( 2 0 1 7 1 8 π ) ⋯ sin ( 2 0 1 7 4 0 3 2 π ) ] θ + α = 2 π → sin ( θ ) = − sin ( 2 π − α ) x . y = 2 1 n = 1 ∏ 2 0 1 6 sin ( 2 0 1 7 2 n π ) = ( 2 1 ) 2 0 1 6 ( − 1 ) 1 0 0 8 [ n = 1 ∏ 2 0 1 6 sin ( 2 0 1 7 n π ) ] x . y = ( 2 1 ) 2 0 1 6 ( − 1 ) 1 0 0 8 . y x = ( 2 1 ) 2 0 1 6 x 1 = ( 2 ) 2 0 1 6 = a b A + B = 2 0 1 8
Just to get something posted, I used the identity here to get an answer of
2 2 0 1 7 − 1 = 2 2 0 1 6 ⟹ a + b = 2 + 2 0 1 6 = 2 0 1 8 .
A variety of proof techniques are provided in the link, including a Chebyshev-inspired one.
@Trevor Arashiro , post your solution!
Log in to reply
Done! I solved your problem this exact way, but I divided the linear term (2017) by the lead term. Then input my answer forgetting I divided by 2 2 0 1 6 .
But now I realize that this is correct but not for the corect reasons.
Log in to reply
Best line: T 2 0 1 7 ( x ) − 1 = 2 2 0 1 6 x 2 0 1 7 + stuff − 1
Problem Loading...
Note Loading...
Set Loading...
Let z = e i θ = x + i y . Then:
cos ( ( 2 n + 1 ) θ ) = R e ( z 2 n + 1 ) = k = 0 ∑ n ( 2 k 2 n + 1 ) x 2 ( n − k ) + 1 ( i y ) 2 k = k = 0 ∑ n ( − 1 ) k ( 2 k 2 n + 1 ) x 2 ( n − k ) + 1 ( 1 − x 2 ) k
which we denote as f ( x ) . It's easy to see that:
f ( x ) = a 2 n + 1 x 2 n + 1 + … + a 1 x 1 . . . ( 1 )
where
a 1 = ( − 1 ) n ( 2 n 2 n + 1 ) = ( − 1 ) n ( 2 n + 1 ) . . . ( 2 )
On the other hand, since cos ( ( 2 n + 1 ) θ ) = 2 1 ( z 2 n + 1 + z 2 n + 1 1 ) = 1 + 2 1 ( z 2 n + 1 + z 2 n + 1 1 − 2 )
= 1 + 2 z 2 n + 1 1 ( z 2 n + 1 − 1 ) 2 and
( z 2 n + 1 − 1 ) 2 = k = 0 ∏ 2 n ( z − e 2 n + 1 2 k π i ) 2 = k = 0 ∏ 2 n ( z − e 2 n + 1 2 k π i ) ( z − e 2 n + 1 − 2 k π i )
= k = 0 ∏ 2 n ( z 2 + 1 − 2 z cos ( 2 n + 1 2 k π ) )
We also have:
f ( x ) = 1 + 2 1 k = 0 ∏ 2 n ( z + z 1 − 2 cos ( 2 n + 1 2 k π ) )
= 1 + 2 2 n k = 0 ∏ 2 n ( x − 2 cos ( 2 n + 1 2 k π ) ) . . . ( 3 )
Now we compare the expressions ( 1 ) and ( 3 ) for f ( x ) . We see from ( 1 ) that the constant term in ( 3 ) is zero. Therefore:
2 2 n k = 0 ∏ 2 n cos ( 2 n + 1 2 k π ) = 1 ⟹ k = 0 ∏ 2 n sec ( 2 n + 1 2 k π ) = 2 2 n
In the problem, we are given n = 1 0 0 8 , so the answer to the problem would be 2 2 ⋅ 1 0 0 8 = 2 2 0 1 6 . Thus a = 2 , b = 2 0 1 6 , a + b = 2 0 1 8 .